Crystallographic ordering of aluminium in laueite at Hagendorf-Süd. (2nd January 2018) - Grey, I. E.; Keck, E.; Mumme, W. G.; MacRae, C. M.; Price, J. R.; Glenn, A. M.; Davidson, C. J.
Abstract: Crystals of laueite, Mn 2+ Fe2 3+ (PO4 )2 (OH)2 ·8H2 O, from the Cornelia mine open cut, Hagendorf Süd, Bavaria, are zoned due to aluminium incorporation at the iron sites, with analysed Al2 O3 contents varying up to 11 wt.%. Synchrotron X-ray data were collected on two crystals with different Al contents and the structures refined. The laueite structure contains two independent Fe 3+ -containing sites; M 2 and M 3, which alternate in 7 Å corner-connected octahedral chains. The coordination polyhedra are different for the two sites, M 2O4 (OH)2 and M 3O2 (OH)2 (H2 O)2 respectively. The structure refinements show that Al preferentially orders into site M 3. Refined site occupancies for M 2 and M 3 for the two crystals are: for crystal L-1, M 2 = 0.70(1) Fe + 0.30(1) Al, M 3 = 0.54(1) Fe + 0.46(1) Al and for crystal L-2, M 2 = 0.67(1) Fe + 0.33(1) Al, M 3 = 0.48(1) Fe + 0.52(1) Al. For crystal L-2, the octahedral chains have dominant Fe in M2, alternating with dominant Al in M 3 along the chain, an ordering phenomenon not previously reported for laueite-related minerals.